Pengaruh Harga, Desain Produk, Kualitas Produk Dan Citra Merek Terhadap Keputusan Pembelian Konsumen Pada Produk UKM Di Yogyakarta - Dwi Wahyu Pril Ranto (Universitas Muhammadiyah Yogyakarta, 2014)
The purpose of this study was to examine the effect of pricing, product design, product quality and brand image on consumer purchasing decisions on products of SMEs in Yogyakarta. The population in this study is that consumers who shop for products of SMEs in Yogyakarta. Samples in this the research are consumers who visit shopping at the handicraft center of Kasongan Bantul. This study used convenience sampling technique that is because of the ease of sampling. The results showed that the variables of price, product design and product quality significantly influence purchasing decisions at SMEs Products in Yogyakarta. While the brand image does not significantly influence the purchasing decisions on products of SMEs in Yogyakarta. These results show that consumers in making purchasing decisions more expensive variable price, design and quality of the products to be bought. As for the image of the brand is not so considered on the grounds that when consumers buy products of SMEs, which are seen affordable prices and the quality of its products according to expectations.Keywords: Price, Product Design, Product Quality, Brand Image, Buying Decision.